Insights Into Various Aspects of Oral Health 2017
DOI: 10.5772/intechopen.68801
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Periodontal Diseases in Consanguineous Marriages

Abstract: Periodontitis is deined as an inlammatory disease of supporting tissues of teeth characterized by progressive destruction of the periodontal ligament and alveolar bone. Periodontal manifestations of these genetic disorders or syndromes, such as familial and cyclic neutropenias, granulomatous disease, agranulocytosis, Langerhans' cell disease, glycogen storage disease, hypophosphatasia, leucocyte adhesion deiciency, and Papillon-Lefèvre, Chédiak-Higashi, Cohen, Ehlers-Danlos, Marfan, Down, Haim-Munk, and Kindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Pedigree analysis studies with genetic expression analysis using methods like In situ -hybridization expression technique,[ 24 ] whole-exome sequencing[ 25 ] focusing on the influence of molecular pattern on dental evolution correlated with morphological variations can help in characterization of these isolated anomalies. Although in this study individuals with syndromes or known congenital diseases were excluded to eliminate the possibility of congenital anomalies arising from these syndrome associated etiology, it should not be underestimated that studies have also shown many syndromes such as Haim-Munk[ 26 ] and Papillon–Lefèvre syndromes,[ 27 ] Ehler-Danlos syndrome,[ 28 ] Chediak–Higashi syndrome[ 29 ] presenting with oral manifestations are closely related to consanguineous marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Pedigree analysis studies with genetic expression analysis using methods like In situ -hybridization expression technique,[ 24 ] whole-exome sequencing[ 25 ] focusing on the influence of molecular pattern on dental evolution correlated with morphological variations can help in characterization of these isolated anomalies. Although in this study individuals with syndromes or known congenital diseases were excluded to eliminate the possibility of congenital anomalies arising from these syndrome associated etiology, it should not be underestimated that studies have also shown many syndromes such as Haim-Munk[ 26 ] and Papillon–Lefèvre syndromes,[ 27 ] Ehler-Danlos syndrome,[ 28 ] Chediak–Higashi syndrome[ 29 ] presenting with oral manifestations are closely related to consanguineous marriage.…”
Section: Discussionmentioning
confidence: 99%
“…The sky-scraping practices of consanguineous marriages in our community are attributable to social practices, ignorance of the general population about associated adversaries, and reluctance to discuss such momentous issues. A matter of concern is that Pakistan ranked 149 th among 179 countries in 2015 on the Maternal Mortality Ratio Index, which is somehow pertinent to consanguineous marriages and congenital malformations as well [ 19 , 20 ]. Perveen et al conducted a similar study in tertiary care institute at Karachi and the lion's share turned out to be neural tube defects widely attributable to consanguinity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%